2021
DOI: 10.1089/hum.2020.105
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge of Gene Therapy for Neurological Diseases: Strategies and Tools to Achieve Efficient Delivery to the Central Nervous System

Abstract: For more than 10 years, gene therapy for neurological diseases has experienced intensive research growth and more recently therapeutic interventions for multiple indications. Beneficial results in several phase 1/2 clinical studies, together with improved vector technology have advanced gene therapy for the central nervous system (CNS) in a new era of development. Although most initial strategies have focused on orphan genetic diseases, such as lysosomal storage diseases, more complex and widespread conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 208 publications
(219 reference statements)
0
26
0
Order By: Relevance
“…These extensive studies provided strong support for CYP46A1 as a therapeutic target and suggested that a one-time CYP46A1 delivery approach could be translatable to human patients. Feasibility and safety proof-of-concept experiments in non-human primates are ongoing in preparation for the submission of a first clinical application in human patients ( Piguet et al, 2020 ).…”
Section: Genetic Targeting Of Cyp46a1 Expressionmentioning
confidence: 99%
“…These extensive studies provided strong support for CYP46A1 as a therapeutic target and suggested that a one-time CYP46A1 delivery approach could be translatable to human patients. Feasibility and safety proof-of-concept experiments in non-human primates are ongoing in preparation for the submission of a first clinical application in human patients ( Piguet et al, 2020 ).…”
Section: Genetic Targeting Of Cyp46a1 Expressionmentioning
confidence: 99%
“…In vivo gene therapy for leukodystrophies requires therapeutic gene transfer to the CNS which is compromised by the skull, the blood – brain barrier (BBB) and cerebrospinal fluid (CSF) – brain barrier (CBB). Delivery methods for rAAV to the brain include direct intraparenchymal (IP) injection, intracerebroventricular (ICV), lumbar intrathecal (IT) intra cisterna magna targeted intrathecal (ICM) and IV injections as well as nasal delivery which have been addressed in excellent recent reviews ( Hocquemiller et al, 2016 ; Piguet et al, 2017 , 2020 ; Hudry and Vandenberghe, 2019 ). In the following section, we review the advances in understanding of AAV vector targeting to provide context for the likely dominance of such gene therapy vector strategies for treating leukoencephalopathies in the future.…”
Section: In Vivo Gene Therapymentioning
confidence: 99%
“…Delivery is the major issue for central nervous system therapies in general, and particularly for gene therapy, the blood brain barrier restricts the passage of vectors thus strategies to bypass this obstacle are a central focus of research. Gene therapy products can be tailored to solve the pathophysiological mechanisms, including the use of gene replacement, gene silencing, transplicing, modulation of cellular pathways to improve phenotype or expression of suicide gene (Piguet et al 2021). There are only few gene therapies approved for the management of neurological disorders including two for SMA (Zolgensma-Novartis and Spinraza-Biogen) (Servais et al 2021).…”
Section: Precision Medicine: Aetiology-based Preventive Treatments and In Progress Treatmentsmentioning
confidence: 99%